3D digital analysis of magnetic force-driven orthodontic tooth movement. Issue 11 (November 2019) - Kuwajima, Yukinori; Ishida, Yoshiki; Lee, Cliff; Mayama, Hisayo; Satoh, Kazuro; Ishikawa-Nagai, Shigemi
Abstract: With the introduction of rare earth magnets like neodymium-iron-boron (NdFeB), it has become possible to produce small magnets with high forces, necessary for its usage in the field of dentistry, such as for orthodontic tooth movement. The ultimate goal of this project is to establish magnetic force-driven orthodontic treatment as a future treatment modality for comprehensive orthodontic treatment. In order to utilize magnets for orthodontic treatment, we must first understand the characteristics of tooth movement created by magnetic forces. In this study, we aimed to digitally assess the efficacy of magnetic attraction and repulsion forces by means of a 3D digital analysis of movement (distance, direction, angulation and duration) and rotation (yaw, pitch and roll) of the crown and root of teeth in an ex vivo typodont model. We performed space closure and space gain treatment of maxillary central incisors (n = 30) and analyzed the movement and rotation of the teeth and root apex with 3D digital analysis. The results of the typodont model indicated significant differences on amount, speed and rotation of tooth and root movement created by magnetic attraction and repulsion forces. We also mimicked a moderate crowding typodont case and successfully treated it with a combination of attraction and repulsion magnetic forces. The moderate crowding case utilized magnets and a titanium archwire to guide the planned tooth movements and prevent undesired or unexpected movement. Further ex vivo experiments and considerations for biosafety will be necessary to investigate magnet force-driven orthodontics as a future modality of orthodontic treatment. Abstract : Dentistry; Dental materials; Medical imaging; Health technology;Magnetic forces; NdFeB magnets; Orthodontic tooth movements; Force control